Determinants of the performance of traditional Chinese medicine clinics in Taiwan. Issue 4 (April 2019) - Chang, Shun-Chiao; Lin, Chi-Feng; Yeh, Ta-Chun; Chang, Chun-Wei
Highlights: TCM clinics that have more physicians can attract more patients. Larger clinics enjoy the advantage of economies of scope from the greater number of divisions as more specialized departments attract more patients. An increase in the unemployment rate strengthens the demand for medical services. The global budget system plays a key role in suppressing the revenue of TCM clinics through the peer review mechanism. Abstract: The study attempts to investigate the features and determinants of the performance of Taiwanese Traditional Chinese Medicine (TCM) Clinics with data for 4905 TCM clinics over the 1998 to 2012 period. The empirical results from the fixed effects model and the Hausman-Taylor Model with cluster-robust standard errors reveal several interesting findings. First, consumer characteristics such as the frequency of disabling injuries has positive impacts on the volume of medical services provided by TCM clinics. These results imply that people are likely to select TCM as the option for medical treatment when they face the occurrence of physical injury in Taiwan. In addition, the scale measurements for TCM clinics including the numbers of physicians, medical personnel and divisions have significantly positive effects on the performance of TCM clinics, while their survival length also has the same effect. Finally, the global budget system under the NHI plays a key role in suppressing the revenue of TCM clinics through the peer review mechanism.